Magnetic Properties of an Iron Meteorite (Yamato-75031) and a Pallasite (Yamato-74044) - Nagata, Takesi (1978)
P(論文) The thermomagnetic curve of the matrix phase of Yamato-75031 (iron meteorite) reveals that the major constituent is 15% Ni plessite and the minor one is 8% Ni kamacite, which correspond respectively to the α-phase of matrix plessite and the Widmanstatten kamacite plates. The thermomagnetic curve of the metal part matrix of Yamato-74044 (pallasite) shows that the major constituent is 6.6% Ni kamacite. The matrix of both samples contains the taenite phase of about 30% Ni in weight. departmental bulletin paper